A STUDY ON CLASSROOM TEACHERS' SELF-EFFICACY İN CONDUCTING RELIGIOUS CULTURE AND MORAL KNOWLEDGE LESSONS - Bozkurt, Eyup; Toker, Oguzhan; Sahin, Cansu (Escola Superior Dom Helder Camara, 2025)
This study examines the self-efficacy levels of classroom teachers in conducting Religious Culture and Moral Knowledge (RCMK) lessons. The RCMK course is important for individuals' spiritual and cultural development and is taught by classroom teachers in cases where subject-specific teachers are unavailable. The research was conducted with 184 classroom teachers working in Elaz & imath;& gbreve;, and a validated and reliable scale was used as the data collection tool. Analyses performed using the SPSS program revealed that teachers' self-efficacy perceptions regarding the RCMK course were slightly above the moderate level. Teachers found themselves competent in terms of knowledge and application skills but indicated a need for support in some areas. The findings suggest that strengthening both pre-service and in-service training programs could enhance teachers' effectiveness in delivering the RCMK course. This study aims to guide future efforts to improve teachers' competencies in this area.
Keywords: Religious Culture and Moral Knowledge (RCMK)